2021
DOI: 10.4081/ejh.2021.3323
|View full text |Cite
|
Sign up to set email alerts
|

The MEG3 lncRNA promotes trophoblastic cell growth and invasiveness in preeclampsia by acting as a sponge for miR-21, which regulates BMPR2 levels

Abstract: Preeclampsia (PE) is one of the leading causes of maternal morbidity and mortality in pregnant women. This study aimed to investigate the potential impact and regulatory mechanisms of bone morphogenetic protein receptor 2 (BMPR2) on the progression of PE. We obtained placental tissues from pregnant women with PE and normal pregnant women, and the results showed that BMPR2 was expressed at low levels in the tissue from PE women. Genetic knockdown of BMPR2 increased the proliferation and invasion of cultured tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Studies have shown that MEG3 affects trophoblast invasion and apoptosis by sponging miR-21, miR-210, and miR770. [50][51][52] SNHG16 was first described as an oncogenic factor. [53] It has been reported that SNHG16 regulates the proliferation, invasion, and migration of multiple cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MEG3 affects trophoblast invasion and apoptosis by sponging miR-21, miR-210, and miR770. [50][51][52] SNHG16 was first described as an oncogenic factor. [53] It has been reported that SNHG16 regulates the proliferation, invasion, and migration of multiple cells.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was performed as in our previous report. 50 Protein extracts from cells were prepared in RIPA buffer (Beyotime) containing 1% NP-40 (Beyotime) and a cocktail of protease and phosphatase inhibitors (Beyotime). Protein concentrations were determined using the Bio-Rad protein assay (Bio- Rad, Hercules, CA, USA; 500-0006).…”
Section: Methodsmentioning
confidence: 99%